The military and colonial destruction of the Roman landscape of North Africa, 1830-1900 - Greenhalgh, Michael (History of warfare, 2014)
The French pursued victory and colonisation amid a Roman landscape little affected down the centuries by local inhabitants. In the space of two generations they destroyed much of it, re-using its materials to create security and a modern prosperity.